PENURUNAN NILAI COD PADA PENGOLAHAN LIMBAH LATEKS SECARA ANAEROBIK - Leopold M Seimahuira (Balai Besar Industri Hasil Perkebunan, 2016)
The study examined the reduction of COD level on latex waste using anaerobic reactor. CODlevel reduction is tested on several hydraulic retention times, i.e. 2, 4, 6, 8, and 11 days. On 2, 4, and 6days of retention time, the percentage of COD level reduction is declining however on 8 and 11 days, itis inclining. It is apt to microbe growth phase.Keywords: reactor, hidraulic retention time, COD